1983
DOI: 10.1097/00006842-198303000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Treatment of High Blood Pressure: III. Follow-Up Results and Treatment Recommendations

Abstract: This article is the third in a series of studies designed to evaluate systolic blood pressure biofeedback and relaxation in the treatment of elevated blood pressure. It reports on the posttreatment follow-up results. The main findings were that patients who received the behavioral treatments could achieve and sustain reductions in blood pressure for at least 18 months. Furthermore, a number of patients who were receiving diuretic therapy to control their pressures were able to maintain reduced pressure for at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Only a few studies have analyzed the effects of a psychologic treatment combining two techniques (11,(18)(19)(20), and follow-up analysis was performed in even fewer (18,20). Thus, our data not only confirm results obtained elsewhere, they demonstrate a significant, long-lasting effect of a complex-but nevertheless feasible-behavioral program to lower high blood pressure in a large number of patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Only a few studies have analyzed the effects of a psychologic treatment combining two techniques (11,(18)(19)(20), and follow-up analysis was performed in even fewer (18,20). Thus, our data not only confirm results obtained elsewhere, they demonstrate a significant, long-lasting effect of a complex-but nevertheless feasible-behavioral program to lower high blood pressure in a large number of patients.…”
Section: Discussionsupporting
confidence: 85%
“…Techniques such a biofeedback (9)(10)(11), meditation (12)(13)(14), relaxation (15)(16)(17) or a combination of two of these (18)(19)(20) primarily have been used. Most of these studies indicated success in lowering blood pressure for several weeks, but only a minority of them demonstrated effectiveness for a longer period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Control group. The control group provided a source of comparison for nonspecific influences of the therapeutic methods (34), such as anticipation of change (35), attention and care of therapeutic agents (36), therapeutic effect of frequent blood pressure measurements (37), habituation to the measure situation (38), and also the nonspecific therapeutic effects of group pressure and group support (23. 35).…”
Section: Treatmentsmentioning
confidence: 99%
“…Less is known about the long-term effectiveness of relaxation training since few investigators have followed their patients for as long as 1 year after treatment. However those studies reporting follow up of patients, have, on the whole, found maintenance of blood pressure lowering (7,8,(10)(11)(12)(17)(18)(19).…”
Section: Relaxation Training For Workite Hypertension-iimentioning
confidence: 99%